Tai Chi Training may Reduce Dual Task Gait Variability, a Potential Mediator of Fall Risk, in Healthy Older Adults: Cross-Sectional and Randomized Trial Studies - Wayne, Peter M.; Hausdorff, Jeffrey M.; Lough, Matthew; Gow, Brian J.; Lipsitz, Lewis; Novak, Vera; Macklin, Eric A.; Peng, Chung-Kang; Manor, Brad (Frontiers in Human Neuroscience, 2015)
BACKGROUND: Tai Chi (TC) exercise improves balance and reduces falls in older, health-impaired adults. TC’s impact on dual task (DT) gait parameters predictive of falls, especially in healthy active older adults, however, is unknown. PURPOSE: To compare differences in usual and DT gait between long-term TC-expert practitioners and age-/gender-matched TC-naïve adults, and to determine the effects of short-term TC training on gait in healthy, non-sedentary older adults. METHODS: A cross-sectional study compared gait in healthy TC-naïve and TC-expert (24.5±12 yrs experience) older adults. TC-naïve adults then completed a 6-month, two-arm, wait-list randomized clinical trial of TC training. Gait speed and stride time variability (%) was assessed during 90 sec trials of undisturbed and cognitive DT (serial-subtractions) conditions. RESULTS: During DT, gait speed decreased (p<0.003) and stride time variability increased (p<0.004) in all groups. Cross-sectional comparisons indicated that stride time variability was lower in the TC-expert vs. TC-naïve group, significantly so during DT (2.11% vs. 2.55%; p=0.027); in contrast, gait speed during both undisturbed and DT conditions did not differ between groups. Longitudinal analyses of TC-naïve adults randomized to 6 months of TC training or usual care identified improvement in DT gait speed in both groups. A small improvement in DT stride time variability (effect size = 0.2) was estimated with TC training, but no significant differences between groups were observed. Potentially important improvements after TC training could not be excluded in this small study. CONCLUSIONS: In healthy active older adults, positive effects of short- and long-term TC were observed only under cognitively challenging DT conditions and only for stride time variability. DT stride variability offers a potentially sensitive metric for monitoring TC’s impact on fall risk with healthy older adults.